Effective language in study guides at a distance learning institution: bridging the gap between the academic and non-academic culture - Vergie, Malvin Patrick (Stellenbosch Papers in Linguistics Plus, 2015)
This article explores the role of effective language in study guides in bridging the gap between the academic culture represented by lecturers and the non-academic culture represented by students at a distance learning institution (DLI). The study guide has to facilitate the student in the world of a new and sometimes intimidating culture, namely the (tertiary) academic culture. When lecturers write for students, they must have an understanding of the challenges facing distance learning students and write in clear, accessible language. There is little or no face-to-face contact between lecturers and students at a DLI, and teaching takes place mainly by means of printed study material, specifically study guides. However, many students may have trouble understanding the type of language used in study material – essentially, academic language – sometimes because lecturers may not have an understanding of the challenges faced by students at a DLI and/or because they are used to writing in a formal, academic style, which is often not easily accessible to first-year students. The aim of the article is thus to identify the linguistic criteria to which a successful study guide for L2 speakers of English should adhere. In the research conducted for this study, a number of linguistic criteria for effective study guides were identified. These criteria were extracted from literature on effective writing/teaching in general, then discussed briefly in terms of their relevance for the specific purpose of writing effective study guides. Finally, these criteria were applied to critically evaluate the language used in three study guides used at a DLI.